A new species of Paraputo Laing (Hemiptera: Coccomorpha: Pseudococcidae) on Fagaceae from southern China - Li, Yuang; Zheng, Xinyi; Wu, San-An (Zootaxa, 2024)
A new species of mealybug (Hemiptera: Coccomorpha: Pseudococcidae), Paraputo nanlingensis Li & Wu, sp. n., is recorded on Fagaceae from Guangdong Province, China. The adult female is described and illustrated, and an identification key is provided to separate the adult females of Paraputo species known from China.